ChemInform Abstract: Unravelling the Proton Conduction Mechanism from Room Temperature to 553 K in a 3D Inorganic Coordination Framework. Issue 51 (December 2015) - Wang, Yaxing; Tao, Zetian; Yin, Xuemiao; Shu, Jie; Chen, Lanhua; Sheng, Daopeng; Chai, Zhifang; Albrecht‐Schmitt, Thomas E.; Wang, Shuao
Abstract: HNd(IO3 )4 is prepared by hydrothermal reaction of Nd2 O3, H5 IO6, and H2 O (autoclave, 160 °C, 3 d).